Analisys of the factors that influence the adoption and use of communication technologies for second hand P2P consumption - Blaz, Claudia Lorena Cárdenas (Universidade Federal de São Carlos, 2024)
The reuse of any product “as is” is closely linked to the concept of solid waste prevention, sustainable consumption and consequent reduction of environmental impact, aligned with the principles of the circular economy. The consumption of second-hand products is an alternative social practice that encourages reuse. It is currently being energized and facilitated by the development of business models based on platforms, mediated by Internet access and the proliferation of electronic devices. Considering the growing popularity of the consumption of used goods through digital platforms, academics from different contexts have addressed consumer behavior in this new context, given its impact on society and the environment. Given the lack of academic evidence from representative emerging scenarios such as Brazil, the objective of this study is to evaluate the adoption and use of the WhatsApp Instant Messaging Platform (IMP) for the purchase or sale of second-hand products (SHP) peer-to-peer (P2P). To achieve the stated objective, a systematic review of the literature was first carried out, with the aim of addressing key questions about motivations, barriers and trends in this emerging phenomenon. We find that consumers are motivated by economic, convenience, ideological and sustainable factors when they decide to purchase second-hand goods. Barriers to secondhand consumption on virtual platforms are identified, including product uncertainty, seller uncertainty, desire for new products, and negative physical contagion. Strategies to overcome these barriers involve face-to-face transactions, emphasizing product packaging, highlighting product quality, and promoting environmental awareness. In the second part of this research, a comprehensive assessment of the adoption and use of IMP Whatsapp for the purchase and sale of SHP was conducted. The factors that influence consumer behavior were investigated using the Expanded Unified Theory of Acceptance and Use of Technology (UTAUT2) as a theoretical basis. Our findings reveal that effort expectancy, hedonic motivations, initial trust, and habitual use positively and significantly affect the intention to use IMP for secondhand transactions. On the contrary, perceived risk negatively affects this behavioral intention, highlighting the need to mitigate users' concerns to encourage participation in second-hand transactions through these platforms. The theoretical contributions of the study highlight the importance of adapting existing theories to understand consumer behavior in the digital landscape, providing valuable information for researchers, practitioners and policymakers. From a practical point of view, the findings can guide companies and instant messaging platform developers to develop user-centric features and marketing strategies tailored to the second-hand market.
Análise dos fatores que influenciam a adoção e uso de tecnologias de comunicação para consumo P2P de segunda mão
Keywords: Economia circular; Circular Economy; Produtos de segunda mão; Second hand products; Plataformas on-line; Online plataforms; UTAUT2; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA